Integrating Character Education and Global Citizenship in the Merdeka Curriculum: A Systematic Review of Challenges and Strategies - Ariani Songli; Suyato Suyato; Ranita Eka Desti Rahmawati; Maria Antoneta Karbeka; Wingkolatin Wingkolatin (Research, Training and Philanthropy Institution Natural Aceh, 2026)
This study examines how character education and global citizenship education are integrated into Indonesia’s Merdeka Curriculum and identifies the main implementation challenges and strategies. Using a systematic literature review, the study analyzed ten Scopus-indexed articles published between 2020 and 2025 through thematic analysis. The findings show that the Merdeka Curriculum integrates character education through the Pancasila Student Profile, project-based learning, and contextual activities, while global citizenship is introduced through themes such as climate change, poverty, social inequality, cultural diversity, and digital citizenship. Three dominant issues emerge: limited teacher readiness, unequal digital infrastructure, and difficulty aligning global perspectives with local and national values. The review concludes that successful implementation requires continuous teacher professional development, stronger digital support, and more contextual curriculum design that connects global issues with local realities without weakening Pancasila-based identity and student character formation in everyday school practice at all levels of Indonesian education today and beyond sustainably.